2010
DOI: 10.1016/j.mce.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of estrogen receptor-related receptor alpha and gamma in human glioma and astrocytoma cells

Abstract: The purpose of this study was to examine expression and function of estrogen receptor-related receptors (ERRs) in human glioma and astrocytoma cell lines. These estrogen receptor-negative cell lines expressed ERRα and ERRγ proteins to varying degree in a cell context dependent manner, with U87MG glioma cells expressing both orphan nuclear receptors. Cell proliferation assays were performed in the presence of ERR isoform-specific agonists and antagonists, and the calculated EC50 and IC50 values were consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
(39 reference statements)
2
17
0
1
Order By: Relevance
“…Given the crucial role of ESRRA in the regulation of energy metabolism, it is not surprising that it can accelerate cancer cell proliferation. Until now, many reports have suggested its potential involvement in the regulation of cancer cell proliferation (11)(12)(13)(14). Additionally, Wu et al (45) have demonstrated that an inverse agonist of ESRRA, XCT-790, can also induce cell death in a multidrug resistance cell line HepG2 (human liver hepatocellular carcinoma cell line).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the crucial role of ESRRA in the regulation of energy metabolism, it is not surprising that it can accelerate cancer cell proliferation. Until now, many reports have suggested its potential involvement in the regulation of cancer cell proliferation (11)(12)(13)(14). Additionally, Wu et al (45) have demonstrated that an inverse agonist of ESRRA, XCT-790, can also induce cell death in a multidrug resistance cell line HepG2 (human liver hepatocellular carcinoma cell line).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, an increased level of ESRRA is linked to poor prognosis of breast, ovarian, and prostate tumors (7,9,10). Several reports suggest that the pharmacological modulation of ESRRA activity with specific inverse agonists such as XCT790 reduces proliferation of cell lines derived from breast, glial, lung, and cervical tumors (11)(12)(13)(14). Using the transwell assay, Zhao et al (15) have shown that ESRRA promotes cancer cell migration and invasion.…”
mentioning
confidence: 99%
“…Since the 1980s, several investigators have attempted to identify steroid hormone receptors in normal human brain cells and in human glioma and glioblastoma cells, as well as in rat glial and glioma cell lines (42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Classical ERs and/or progestin, glucocorticoid, and androgen receptors are expressed in normal rat glial cells (26,42).…”
Section: Steroid Receptors In Normal Glial Cells and Glioma Cellsmentioning
confidence: 99%
“…Genistein, an isoflavone that binds preferentially to ERβ and that also inhibits protein tyrosine kinases and topoisomerase II, rapidly inhibited DNA synthesis in human glioma cells in a concentration-dependent manner (71). The SERM tamoxifen, which can have both estrogenic and antiestrogenic effects, also inhibits glioma cell proliferation and induces apoptosis in vitro (51,(72)(73)(74). Interestingly, both tamoxifen and a benzopyranone with SERM activity, CC-8490, have been reported to induce apoptosis in vitro and in vivo in ER-negative glioma cells (75).…”
Section: Actions Of Steroid Hormone Receptor Agonists and Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation